Alternative Therapies of the Banjar People for Children with Fevers - Esme Anggeriyane; Hamzah Hamzah; Nurhikmah Nurhikmah (Jurnal Keperawatan Indonesia, 2024)
Fevers often occur in children under five years of age due to the immature formation of their immune systems. Such fevers signify that something unusual is happening in the body, often due to illness. Parents conduct various management techniques, such as medical or traditional treatments, based on their beliefs. Banjar society has a health culture known as bapidara, which is used to treat children with fevers presumably attributable to supernatural disturbances. This exploratory research aimed to discover what alternative therapies the Banjar people use to treat children with fevers. This qualitative study used a transcendental phenomenological design. Data collection was conducted with eight mothers who had children under the age of five using in-depth interviews. Five themes were identified based on the findings: the mothers’ actions in treating children with fevers, the mothers’ understanding of bapidara as local wisdom, the procedures for performing bapidara, the health progress of the children after bapidara, and factors that influence the choice of bapidara as a traditional treatment to relieve fever. This research can be used as the initial basis for cultural nursing care decisions in the development of complementary therapy for the initial treatment of children with fever at home using medicinal plants tested for their effectiveness as family-centered care.